Surface Modification of Polystyrene with Boronic Acid for Immunoaffinity-Based Cell Enrichment - Shirani, Elham (Langmuir : the ACS journal of surfaces and colloids, 2024)
Obtaining an enriched and phenotypically pure cell population from heterogeneous cell mixtures is important for diagnostics and biosensing. Existing techniques such as fluorescent-activated cell sorting (FACS) and magnetic-activated cell sorting (MACS) require preincubation with antibodies (Ab) and specialized equipment. Cell immunopanning removes the need for preincubation and can be done with no specialized equipment. The majority of the available antibody-mediated analyte capture techniques require a modification to the Abs for binding. In this work, no antibody modification is used because we take advantage of the carbohydrate chain in the Fc region of Ab. We use boronic acid as a cross-linker to bind the Ab to a modified surface. The process allows for functional orientation and cleavable binding of the Ab. In this study, we created an immunoaffinity matrix on polystyrene (PS), an inexpensive and ubiquitous plastic. We observed a 37% increase in Ab binding compared with that of a passive adsorption approach. The method also displayed a more consistent antibody binding with 17 times less variation in Ab loading among replicates than did the passive adsorption approach. Surface topography analysis revealed that a dextran coating reduced nonspecific antibody binding. Elemental analysis (XPS) was used to characterize the surface at different stages and showed that APBA molecules can bind upside-down on the surface. While upside-down antibodies likely remain functional, their elution behavior might differ from those bound in the desired way. Cell capture experiments show that the new surface has 43% better selectivity and 2.4-fold higher capture efficiency compared to a control surface of passively adsorbed Abs. This specific surface chemistry modification will allow the targeted capture of cells or analytes with the option of chemical detachment for further research and characterization